DISEMINASI PEMANFAATAN ECENG GONDOK (EICHORNIA CRASSIPES) MENJADI PUPUK ORGANIK CAIR SEBAGAI IMPLEMENTASI PERTANIAN DAN PERAIRAN BERKELANJUTAN - Putri, Harmin Adijaya; Kisma, Kisma; Mardiah, Mardiah; Astaman, Putra (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2023)
The purpose of this service program is to provide information and empower the community through dissemination in the form of environmentally friendly agricultural technology extension activities in the hope of increasing food crop production in a sustainable manner. Lampulung Village is one of the villages that has the potential for extensive agricultural land, but the community still dominantly uses chemical fertilizers which have a negative impact on the environment. Therefore, we took the initiative to carry out this counseling activity because Lampulung Village has a very abundant water hyacinth (Eichornia crassipes) population. The potential of water hyacinth as an environmentally friendly liquid fertilizer has a nutrient content that is more easily absorbed by plants, and the manufacturing process can be made in a relatively short time at a relatively low cost. The method used in this service is counseling. Where this activity is carried out through 3 stages, namely the preparation stage, the extension implementation stage, and the evaluation stage. The results of this community service are that the community increasingly understands the importance of preserving the aquatic environment, one of which is through the use of water hyacinth as a liquid organic fertilizer to replace chemical fertilizers, so as to realize sustainable agriculture.